2020
DOI: 10.3390/polym12102305
|View full text |Cite
|
Sign up to set email alerts
|

Control of Macromolecule Chains Structure in a Nanofiber

Abstract: Mechanical property is one of the most important properties of nanofiber membranes. Electrospinning is widely used in the preparation of nanofibers due to its advantages such as good stability and easy operation. Compared with some nature silk, the mechanical properties of nanofibers prepared by electrospinning are poor. Based on the principle of vortex spinning and DNA structure, this paper designed an air vortex electrospinning device that can control the structure of macromolecular chains in nanofibers. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Appropriate mechanical properties of electrospun membrane are necessary for its application [ 44 , 45 ]. Therefore, the effect of the BP@SF on the mechanical properties of the electrospun membrane were investigated, using a tensile testing machine ( Figure 4 c).…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate mechanical properties of electrospun membrane are necessary for its application [ 44 , 45 ]. Therefore, the effect of the BP@SF on the mechanical properties of the electrospun membrane were investigated, using a tensile testing machine ( Figure 4 c).…”
Section: Resultsmentioning
confidence: 99%
“…The air vortex in the electrospinning process, fig. 1, can improve the mechanical properties of nanofiber membrane [12]. In our previous experiment, we found that through this method, the mechanical properties of nanofiber membranes are significantly improved.…”
Section: Introductionmentioning
confidence: 86%
“…It is a known fact that the internal structure of nanofibers can greatly affect nanofiber's properties, ordered distribution, and well orientation of macromolecules in the nanofiber will enhance its mechanical, thermal, and electronic properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a simple and straightforward fabrication process, electrospinning is widely adopted in producing nanofibers [2][3][4][5][6], whereas its low output has dramatically hindered its industrial applications. To get rid of the shortcoming of the electrospinning, the bubble electrospinning was appeared as the most promising technology for mass-production of various functional nanofibers [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%